THE INFLUENCE OF ISLAMIC-BASED CONTEXTUAL LEARNING ON SCIENCE MOTIVATION AND ENVIRONMENTAL CARE FOR ELEMENTARY SCHOOL 56 PARADAYYA STUDENTS - Pirman Syah; Muh. Rapi; Andi Maulana (LP2M IAIN Sultan Amai Gorontalo, 2026)
This study addresses the challenge of integrating religious values into science learning, a gap often resulting in low student engagement and weak character development. The research examines the effect of an Islamic-based contextual teaching and learning (CTL) model on the science learning motivation and environmental care attitudes of Grade VIII students at SMP Negeri 2 Takalar. Using a quantitative approach with a quasi-experimental design, the study involved two groups: an experimental group receiving Islamic-based CTL and a control group taught with conventional methods. Data were collected through pretest–posttest measurements and analysed using descriptive statistics, prerequisite tests, and hypothesis testing with SPSS 24. The results revealed that the experimental group experienced a significant improvement in science learning motivation (25.14% increase) and environmental care attitude (25.43% increase), compared to the control group’s modest gains of 9.44% and 9.70%, respectively. Statistical analysis confirmed that these differences were significant, indicating the effectiveness of Islamic-based CTL in fostering cognitive engagement and positive behavioural change. It is concluded that integrating Islamic values within CTL strengthens students’ intrinsic motivation and moral responsibility toward environmental stewardship. The model thus contributes to the pedagogical framework of CTL by embedding spiritual values into practical learning contexts. This research provides theoretical enrichment for CTL models and practical guidance for educators seeking holistic approaches to science education. Future studies should explore similar integrations across subjects and educational levels to reinforce sustainable, value-based education.